Serum LDH level may predict outcome of chronic lymphocytic leukemia patients with a 17p deletion： a retrospective analysis of prognostic factors in China - Li, Heng; Xiong, Wenjie; Liu, Huimin; Yi, Shuhua; Yu, Zhen; Liu, Wei; Lyu, Rui; Wang, Tingyu; Zou, Dehui; Li, Zengjun; Qiu, Lugui (Chinese journal of cancer research, 2017)
Objective： This study aims to evaluate the natural history of patients with chronic lymphocytic leukemia （CLL） and a 17p deletion （17p-） and identify the predictive factors within this subgroup. Methods： The sample of patients with CLL were analyzed by fluorescence in situ hybridization for deletions in chromosome bands 1 lq22, 13q14 and 17p13; trisomy of bands 12q13; and translocation involving band 14q32. The data from 456 patients with or without a 17p- were retrospectively collected and analyzed. Results： The overall response rate （ORR） in patients with a 17p- was 56.9%, and patients with a high percentage of 17p- （defined as more than 25% of cells harbouring a 17p-） had a lower ORR. The median overall survival （OS） in patients with a 17p- was 78.0 months, which was significantly shorter than the OS in patients without this genetic abnormality （median 162.0 months, P〈0.001）. Within the subgroup with a 17p-, the progression-free survival was significantly shorter in patients at Binet stage B-C and patients with elevated lactate dehydrogenase （LDH）, B symptoms, unmutated IGHVand a high percentage of 17p-. Conclusions： These results indicated that patients with a 17p- CLL have a variable prognosis that might be predicted using simple clinical and laboratory characteristics.